4-Imidazol-1-yl-butane-1-sulfonic acid ionic liquid: Synthesis, structural analysis, physical properties and catalytic application as dual solvent-catalyst - Khaligh, Nader Ghaffari; Mihankhah, Taraneh; Johan, Mohd Rafie; Juan, Joon Ching (Taylor & Francis, 2019)
4-Imidazol-1-yl-butane-1-sulfonic acid (ImBu-SO3H) has been successfully synthetized and fully characterized by FT-IR and high-resolution NMR spectroscopy (1H, 13C). The “plausible” alternative structures of ImBu-SO3H were discussed on the basis of its NMR data. The ionic liquid showed interesting dual solvent-catalyst property, which was studied experimentally for the acetylation of a variety of functionalized alcohols, phenols, thiols, amines and α-tocopherol (α-CTP) as the most active form of vitamin E with acetic anhydride and which provided good yields within a short reaction time. ImBu-SO3H was successfully recycled by product extraction with an average recovered yield of 82% for 5 subsequent runs. The catalytic activity of the recycled ImBu-SO3H showed almost no loss even after five consecutive runs. © 2019, © 2019 Taylor & Francis Group, LLC.